1983
DOI: 10.1002/ijc.2910320102
|View full text |Cite
|
Sign up to set email alerts
|

Diet and colorectal cancer: A case‐control study in Greece

Abstract: A case-control study probing the role of diet on the incidence of colorectal cancer was undertaken in Athens, Greece, in a population characterized by ethnic homogeneity but substantial heterogeneity with respect to dietary habits. The case series consisted of 100 consecutive patients with histologically confirmed colorectal cancer admitted to two large hospitals of Athens during a 16-month period; the control series consisted of orthopaedic patients, admitted to the same hospitals during the same time period,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
95
2
4

Year Published

1990
1990
2008
2008

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 290 publications
(104 citation statements)
references
References 15 publications
3
95
2
4
Order By: Relevance
“…The questionnaire was not validated, since this was not the norm at that time. However, a similar questionnaire has been used in other studies, the results of which have been confirmed in later and larger investigations (Manousos et al, 1983Trichopoulos et al, 1985). Nutrient intakes were estimated using the University of Massachusetts food composition database (Willett et al, 1985) and information on typical portion sizes from a Greek database (Katsouyanni et al, 1991).…”
Section: Methodsmentioning
confidence: 84%
“…The questionnaire was not validated, since this was not the norm at that time. However, a similar questionnaire has been used in other studies, the results of which have been confirmed in later and larger investigations (Manousos et al, 1983Trichopoulos et al, 1985). Nutrient intakes were estimated using the University of Massachusetts food composition database (Willett et al, 1985) and information on typical portion sizes from a Greek database (Katsouyanni et al, 1991).…”
Section: Methodsmentioning
confidence: 84%
“…shown by others (Higginson 1966;Manousos et al 1983; Tajima and Tominaga 1985; Kono et al 1986; Adami et al 1992). Recent publications have suggested that beer drinking may increase the risk of rectal cancer (Kabat et al 1986; Kune et al 1987; Riboli et al 1991), although others found no increase (Manousos et al 1983; Pickle et al 1984;Potter and McMichael 1986;Tuyns et al 1988).…”
mentioning
confidence: 75%
“…Since bivariate correlations between particular food groups and mortality from speci®c diseases over a total of only ten countries do not allow control for mutual confounding, likely to be generated by the inter-relations of the various food groups, we have used a composite score to summarise the postulated in¯uence of diet (including also smoking when needed). Composite scores are often used to describe the likely effects of total diet (Hjermann et al, 1981;Manousos et al 1983;Trichopoulou et al, 1995), and they are also employed in several other areas of clinical research (Alvarez M et al, 1998).…”
Section: Methodsmentioning
confidence: 99%